Fire load occupancy of various zones in an pharmaceutical industry - Yudhistrakumar, Alavandar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Considering the highly flammable and toxic substances, which are stored and used in the various processes for the manufacturing of the finished good in the pharmaceutical industry, it is necessary to know the quantity of flammable/combustible materials used in the chemical factory. Based on the quantification of the materials, its calorific value, we have calculated the fire load for each of the hazardous occupancy zones in the factory. The quantification based on the flammable/combustible substances, which are based on the lowest and highest quantity of material stored in the chemical factory. We have derived the fire load for various zones and found the lowest and highest fire load for the hazardous occupancy in the factory. Further the fire load has been categorized in the form of low/medium/high level hazardous occupancy zones in the chemical factory, which will help us in identifying the most critical fire hazardous zone, which are having the highest chances of catching fire.